Identifying kinase targets of PPARγ in human breast cancer. (3rd July 2021) - Kandel, Anish; Dhillon, Sarinder Kaur; Prabaharan, Chandra Bose; Fatnin Binti Hisham, Syaza; Rajamanickam, Karthic; Napper, Scott; Chidambaram, Saravana Babu; Essa, Musthafa Mohamed; Yang, Jian; Sakharkar, Meena Kishore
Abstract: Breast cancer is the most common cancer in women. Despite advances in screening women for genetic predisposition to breast cancer and risk stratification, a majority of women carriers remain undetected until they become affected. Thus, there is a need to develop a cost-effective, rapid, sensitive and non-invasive early-stage diagnostic method. Kinases are involved in all fundamental cellular processes and mutations in kinases have been reported as drivers of cancer. PPARγ is a ligand-activated transcription factor that plays important roles in cell proliferation and metabolism. However, the complete set of kinases modulated by PPARγ is still unknown. In this study, we identified human kinases that are potential PPARγ targets and evaluated their differential expression and gene pair correlations in human breast cancer patient dataset TCGA-BRCA. We further confirmed the findings in human breast cancer cell lines MCF7 and SK-BR-3 using a kinome array. We observed that gene pair correlations are lost in tumours as compared to healthy controls and could be used as a supplement strategy for diagnosis and prognosis of breast cancer.